Transformation of labor relationships under the globalization influence: new problems of social policy - Приступа, М. В. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2020)
The article examines transformations of labor relationships under the influence of globalization in the context of tasks which consequently emerge in social policies. The introduction of new technologies into the production process and incorporation of countries into the unified economic space predetermine significant changes in the structure of the labor market, as well as in the basic principles of interaction between employers and employees. This results in transformations of labor and social biographies of the latter. General social effects of these transformations are analyzed, as well as their possible negative consequences that require regulation, such as job insecurity, increase in number of cases of forced labor mobility, intensification of social inequalities and alienation. The questions of welfare of wage workers in the following aspects are raised: professional (qualification, career growth, way of organizing the labor process), economic (ensuring a stable and adequate income), social (professional prestige, position in the system of inequalities and life chances), psychological (feeling of security, adaptation to the group of co-workers). Special attention is paid to the questions of formation of the sense of community in the context of labor relationships, as well as of transformation of the role of labor communities in person's social integration. The research results on the manifestations of the described transformations in the Ukrainian society are presented. Based on the estimates regarding further development of these changes, there were identified the key aspects of the efficient social policies, aimed at their compensation, such as ensuring equal access to professional education, possibilities of improvement or switching of professional skills, transformations of values and norms regarding labor relationships, as well as the questions of formation of trust and sense of community, of positive personal and group identification.